EXAMINATION OF TRADITIONAL MARKETS IN SUSTAINING SOCIAL, CULTURAL, AND ECONOMIC INTERACTIONS AMIDST THE DIGITAL ERA - Ramadhan Tanjung , Rizki; Hasanah, Umi; Putri Salsabila , Amanda; Janna Lubis , Radja; Fernanda Desky , Ahmed (PERSPEKTIF: Journal of Social and Library Science, 2024)
This study seeks to examine traditional markets in their role of sustaining social, cultural, and economic interactions within the context of the digital era. This research method employs qualitative techniques, utilizing field observation and conducting interviews with informants, while also integrating theoretical considerations. The findings of this study indicate that numerous traders in the Central Market continue to operate in a traditional manner, resisting contemporary developments. This approach is driven by their desire to foster interaction with buyers, ensuring that customers receive the quality goods they expect. Some traders leverage advancements in the digital age by employing social media to promote their products, ensuring that a wide audience is aware of the high quality of their offerings and can view their stores directly.